2014
DOI: 10.1007/s11999-014-3841-1
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-bearing Synthetic Bone Graft Delivers rhBMP-2 and Promotes Healing of Critical Rat Femoral Segmental Defects

Abstract: pHEMA-nHA-vancomycin preabsorbed with rhBMP-2 may be useful in the repair of critical-size long bone defects prone to infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
11
0
3
Order By: Relevance
“…Furthermore, these data are in agreement with other groups deploying MSCs or BMP-2 from calcium crosslinked alginate into critical-sized bone defects. [14, 20] In light of improved cell survival when using BMP-2 at doses lower than commonly employed in rat bone defects [14, 35, 36] , these findings may enable the use of lower concentrations of MSCs or BMP-2, depending on the availability of cells for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these data are in agreement with other groups deploying MSCs or BMP-2 from calcium crosslinked alginate into critical-sized bone defects. [14, 20] In light of improved cell survival when using BMP-2 at doses lower than commonly employed in rat bone defects [14, 35, 36] , these findings may enable the use of lower concentrations of MSCs or BMP-2, depending on the availability of cells for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The BMP2 preabsorbed onto the pHEMA-nHA-vancomycin composite was continuously released over 8 days, which induced osteogenic differentiation of C2C12 cells [ 30 ]. In critical rat femoral segmental defects in a latter study, the authors showed that the pHEMA-nHA-vancomycin-BMP2 composites could achieve full bridging with substantially mineralized callus and partial restoration of torsional strength [ 122 ]. This carrying material was also used to deliver tetracycline, BMP2/7 heterodimer and RANKL (Receptor activator of nuclear factor kappa-B ligand).…”
Section: Co-delivery Systems For Antibacterial and Osteoinductive mentioning
confidence: 99%
“…На наш взгляд, наиболее разработанным выглядит направление по импрегнации различных биологически активных компонентов в объем и/или на поверхность ксеноматрикса: факторы роста и лекарственные субстанции [41,42,43,44,45,46,47,48,49]. Достаточно актуальным является направление тканевой инженерии, где на поверхность ксеноматериала прививают стволовые клетки [51,52,53,54,55,56,57].…”
Section: результатыunclassified
“…Импрегнация биологически активными веществами Факторы роста [41,42,43,44,45] Антибиотики [46,47] Антибиотики + Факторы роста [48] Бисфосфонаты [49] Плазма, обогащенная тромбоцитами [50] Тканевая инженерия Обогащение ксеноматрикса стволовыми клетками [51,52,53,54,55,56,57] Химическая модификация ксеноматрикса Включение ионов фтора [58] Включение ионов хлора [59] Включение ионов магния [60] Химическая сшивка биополимеров [61] Физическая модификация ксеноматрикса Изменение пористости [62,63] Изменение кристалличности [64] Совершенствование технологии очистки Депротеинизация [65] Извлечение липидов [66] Новые источники ксеноматериала Роговая кость [67] Кролики, лошадь [68] Выполненный анализ показал, что костнопластические материалы ксеногенного происхождения в настоящее время в практической травматологии и ортопедии используются при лечении ограниченного спектра патологий, в отличие от челюстно-лицевой хирургии и стоматологии, где накоплен большой опыт применения этих материалов для замещения костных дефектов, а также сформированы собственные протоколы имплантации. Тем не менее, можно ожидать рост востребованности ксеноматериалов в травматологии и ортопедии, связанный с увеличением клинического спроса на костнопластические материалы, который, в частности, вызван увеличением числа ревизионных операций эндопротезирования, требующих восполнения недостатка костной ткани.…”
Section: направление тип модификации источникunclassified